DEVELOPMENT AND VALIDATION OF TECHNOLOGY FOR TEACHING BASIC LIFE SUPPORT IN CARDIO-RESPIRATORY ARREST - Daniela de Souza Motta; Ricardo Bezerra Cavalcante; Herica Silva Dutra; Angélica da Conceição Oliveira Coelho; Zuleyce Maria Lessa Pacheco; Kelli Borges dos Santos; Fábio da Costa Carbogim (Universidade Federal do Paraná, 2022)
Objective: to develop and validate a multimedia application on a mobile platform for teaching basic support in cardiac arrest to undergraduate health care students. Method: methodological study conducted in two stages: development of the application and content validation by experts. The application was developed based on Contextualized Instructional Design, following the stages of analysis, design, development, and implementation. For the content validation, 11 experts evaluated the application regarding relevance, clarity, coherence, information, presentation, navigability, accessibility, and design. Results: The SBVida application was developed for mobile devices on the Android platform. An overall Content Validity Index of 0.87 was achieved. Conclusion: The SBVida application was developed and validated and can contribute to the preparation and further training of students and professionals from Nursing and other health fields.